EFFECT OF USAGE OF CLIMATE SMART AGRICULTURAL PRACTICES ON RICE FARMERS’ INCOME IN NIGER AND KWARA STATES, NIGERIA - *Ebenehi, O.; Fawole, B.F.; Musab, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study evaluates the effect of usage of climate smart agricultural practices on rice farmers’ income in Niger and Kwara States, Nigeria. Multi-stage sampling technique was used to select 788 respondents for the study. Data were collected through the used of structured questionnaire and analysed using both descriptive and inferential statistics such as percentages and means and propensity score matching (PSM). The result indicated that the majority (with a pooled mean score of (40.8) of the respondents were in their active years of production, and have relatively large household size (9 persons). RBCAPs usage had a positive and significant effect on rice farmers income in the study area, with an average treatment effect on treated (ATT) of N 135,119.96k in terms of income obtained from rice production per hectare by the respondents who use of RBCAPs. The study concluded that RBCSAP users had increased income among small scale rice farmers. The study therefore recommended Female household heads need to be encouraged to key into the practice in order to improve their income base. Income of the users increased by N135119.96k per hectare as a result of usage of RBCAPs, it is therefore recommended that the usage be sustained.